"If you're offered help, take it": A qualitative study examining bariatric patients' experience of telephone‐based cognitive behavioural therapy. Issue 2 (29th November 2020) - Santiago, Vincent A.; Cassin, Stephanie E.; Wnuk, Susan; Du, Chau; Hawa, Raed; Parikh, Sagar V.; Sockalingam, Sanjeev
Summary: The increased recognition of patients' mental health needs after bariatric surgery has resulted in the emergence of accessible psychosocial interventions; however, there is a dearth of literature on patient experience and satisfaction with these interventions. We explored patients' perceptions and experiences of telephone‐based cognitive behavioural therapy (Tele‐CBT) in this qualitative study. Ten participants from the Toronto Western Hospital Bariatric Surgery Program in Toronto, Canada who completed the Tele‐CBT (ClinicalTrials.gov Identifier: NCT02920112) were individually interviewed from November 2014 to June 2016 until thematic saturation occurred (ie, no more new coding groups emerged). Interviews were transcribed, independently coded, checked for discrepancies, and analysed using grounded theory. Four themes emerged: (1) participants were generally satisfied with Tele‐CBT (eg, therapeutic alliance, resources provided, relevance of therapy to their own bariatric journey), (2) participants noticed emotional, cognitive, and behavioural changes following therapy, (3) the optimal time to deliver the Tele‐CBT was when weight loss plateaued, generally at one‐year post‐surgery, and (4) participants found the telephone modality convenient. CBT was generally found to be helpful and the telephone format increased convenience and accessibility. Patients reported learning skills and receiving resources that could help them improve their well‐being following bariatric surgery.